Statistical modelling on the relationship between job performance and employee morale in an organisation / Nagarajah Lee … [et.al.]. - Lee, Nagarajah; Singh, Kuldip; Hj. Ibrahim, Sueb (2004)
The purpose of the study is to explore the interrelationships between morale and the job performance of the employees of ZECON Engineering Berhad. The information gathered was also used to develop a statistical model to explain how the staffs' morale influences their job performance. A total number of 116 staff of ZECON Engineering Berhad were involved in this study. The research design used the self-administered questionnaire as the major data collection method. The findings showed that there was a significant difference in the morale status between the male and female employees where female employees registered a moderately higher score as compared to the male. In this study it was also found that the male employees registered higher job performance as compared to the female employees. Apart from that, this study also revealed that all the five factors, leadership, belongingness, environment, personal development and collegiality contributed significantly to the morale of the employees. The working environment was rated as the most important factor among the five.